Решить уравнение  (2х - 1)(3х+7)-(1+6х)(х+2)=4  

Решить уравнение  (2х - 1)(3х+7)-(1+6х)(х+2)=4  
Гость
Ответ(ы) на вопрос:
Гость
(2х - 1)(3х+7)-(1+6х)(х+2)=4  6х^2+14х-3х-7-(х+2+6х^2+12х)=4 6х^2+11х-7-х-2-6х^2-12х=4 -9-2х=4 -2х=4+9 -2х=13 х=13:(-2) х=-6,5 Ответ:х=-6,5.
Гость
[latex](2x-1)(3x+7)-(1+6x)(x+2)=4[/latex]   [latex]6x^{2}+14x-3x-7-x-2-6x^{2}-12x=4 [/latex]   [latex]6x^{2}+14x-3x-7-x-2-6x^{2}-12x-4=0[/latex]   [latex](6x^{2}-6x^{2})+(14x-3x-x-12x)+(-7-2-4)=0[/latex]   [latex]-2x-13=0[/latex]   [latex]2x=-13[/latex]   [latex]x=-13:2[/latex]   [latex]x=-6,5[/latex] __________________________________________________________________ [latex](2\cdot(-6,5)-1)\cdot(3\cdot(-6,5)+7)-(1+6\cdot(-6,5))\cdot(-6,5+2)=4[/latex]   [latex](-13-1)\cdot(-19,5+7)-(1-39)\cdot(-4,5)=4[/latex]   [latex]-14\cdot(-12,5)-(-38)\cdot(-4,5)=4[/latex]   [latex]175-171=4[/latex]   [latex]4=4[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы